The Influence of Service Quality, Price, Location, Promotion, and Product Quality on Business Partner Satisfaction in Public Areas at Terminal 3 of Soekarno-Hatta Airport PT Angkasa Pura II (Study of Business Partners in 2023 at Soekarno-Hatta Airport) - Mego Setyo Putro; Juliater Simarmata; Salahudin Rafi (Dinasti Publisher, 2024)
This research explores the new strategy adopted by PT Angkasa Pura II as an airport operator to innovate to increase business partner satisfaction in the Departure Public Area of Terminal 3 of Soekarno-Hatta Airport through multiple regression research methods. This research identifies the potential for increasing business partner satisfaction with PT services. Angkasa Pura II, PT Angkasa Pura II through the Commercial Division so that they can run business directly, especially in the Departure Public Area of Terminal 3 of Soekarno-Hatta Airport. By improving service and evaluating commercial aspects, it is hoped that it will be directly proportional to increasing business partner satisfaction PT Angkasa Pura II, This research was carried out through 2 stages of analysis, namely instrument analysis which included validity and reliability tests, and Multiple Regression Analysis. Based on the results of the analysis, it was found that service and price simultaneously or together influence partner satisfaction in the Departure Public Area of Terminal 3 of Soekarno-Hatta Airport by 65%. Based on this data, opportunities to increase business partner satisfaction can still be possible by increasing competence and adjusting commercial aspects or changing business models carried out by PT Angkasa Pura II. Keywords: Business Partner Satisfaction, Terminal 3, Validity Test, Reliability Test, Multiple Regression